MANAJEMEN KEGIATAN BERBAGI PENGE Manajemen kegiatan berbagi pengetahuan Antar santriawati dalam upaya peningkatan karakter - Galur diana; Minto Yuwono (Relevancia: Jurnal Pendidikan dan Pembelajaran, 2025)
This study discusses the management of knowledge sharing activities between female students in order to improve character at SMP AL-Halim Garut. Knowledge sharing is one of the important strategies in the formation of female students' character, especially in an Islamic boarding school-based educational environment. This study uses a qualitative approach with a case study method to analyze how knowledge sharing activities are designed, implemented, and evaluated in a school environment. Data were collected through interviews, observations, and documentation involving teachers, female students, and school administrators. The results of the study indicate that knowledge sharing activities can improve character values ​​such as discipline, responsibility, cooperation, and independence. The implementation of this activity is supported by collaborative learning methods, book studies, group discussions, and mentoring programs between female students. However, there are challenges such as differences in the level of understanding of female students and time constraints in the school curriculum. Therefore, a more structured management strategy is needed so that knowledge sharing activities can run effectively and sustainably.